Chapter A composite indicator to measure regional investment policies on R&D and innovation - Faramondi, Alessandro (Proceedings e report, 2023)
The aim of this work is to illustrate the application of a tool to monitor regional smart specialization strategies, a place-based european approach characterised by the identification of strategic areas for intervention on r&s and innovation as a driving factor for development and territorial competitiveness. Therefore a new classification of enterprises has been defined, that represents all the dimensions of smart specialization, such as innovation, r&s, human capital, business relations, environmental sustainability, ability to drive the territorial development. This work introduces the results of a composite indicator on the microdata of the italian business census 2019, integrated with Istat business registers, identifying a score for each individual enterprises, rather than on aggregates (e.g. territorial). The idea is to have a synthetic value on microdata in order to calculate indicators on aggregates, for example on economic activities of enterprises, defined with respect to new policy needs. The results provide indications of potentials and strategic development trajectories of regional economies. The methodology adopted offer different opportunities for analysis: it's possible to evaluate the areas of smart specialization chosen by each Italian region for the coesion funds' 2021-2027 planning, which dimensions are stronger or weaker on each area, in order to give indications on investments and intervention priorities. It's possible to get an objective analysis of the region or country current situation in terms of research, innovation, industrial structures, skills and human capital. The output of this work is presented through different dashboards of outcome indicators for the Italian smart specialization areas at the regional or national level.